2014
DOI: 10.12693/aphyspola.125.965
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Storage Getter Test for Cu Contaminations in Silicon Wafers Based on ToF-SIMS Measurements

Abstract: This work presents development and results of a storage getter test based on the measurement of the metal concentration by time-of-ight secondary ion mass spectroscopy applied for a low Cu contamination level. It was found that Cu atoms introduced into the as-grown sample by a drive-in anneal at high temperature diuse out from the bulk to the surface within 7 days of storage at room temperature. Annealing steps at low temperature should decrease the time which Cu needs for the outdiusion to the surface. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…2c and 2d for p ++ substrate, respectively. At room temperature, Cu atoms are gettered at the surface for both wafers, due to the high Cu binding energy at the wafer surfaces in agreement also with the observed out-diffusion of Cu to wafer surfaces at room temperature 3 due to the fact that below 600 K, the surface is simply the strongest getterer (Fig. 2).…”
Section: Comparison With Published Experimental Datasupporting
confidence: 82%
See 1 more Smart Citation
“…2c and 2d for p ++ substrate, respectively. At room temperature, Cu atoms are gettered at the surface for both wafers, due to the high Cu binding energy at the wafer surfaces in agreement also with the observed out-diffusion of Cu to wafer surfaces at room temperature 3 due to the fact that below 600 K, the surface is simply the strongest getterer (Fig. 2).…”
Section: Comparison With Published Experimental Datasupporting
confidence: 82%
“…Ref. 3 and references therein. Among the transition metals, Cu is the only one with a strong segregation at the Si surface after a drive-in from the surface to the bulk of the wafer.…”
mentioning
confidence: 99%
“…[2][3][4] It was also demonstrated that metallic impurities can be effectively trapped at oxygen precipitates in the process of gettering. [5][6][7][8][9] All these features of the oxygen precipitates require the control of precipitation in the production process of silicon devices. However, this cannot be optimally executed if the features of oxygen precipitates like their composition are not fully known.…”
mentioning
confidence: 99%
“…This ToF-SIMS 7 day storage Cu getter test is described in detail in Ref. 26. The contamination level was in the range 4 × 10 12 cm −2 to 1.5 × 10 13 cm −2 .…”
Section: Methodsmentioning
confidence: 99%